Multiwalled Carbon Nanotubes Modified with Biocompatible Compounds - Bolbukh, Y.; Gunko, G.; Prikhod’ko, G.; Tertykh, V.; László, K.; Tóth, A.; Koczka, B. (Хімія, фізика та технологія поверхні, 2010)
Oxidized with solution of hydrogen peroxide multiwalled carbon nanotubes (MWCNTs) were modified with 2-hydroxyethylmethacrylate (HEMA) or chitosan (CTS). Morphology and surface properties of the pristine and modified MWCNTs have been investigated. The zeta-potential behaviour of MWCNTs was studied as a function of pH and suspension concentration. After oxidation, the divided nanotubes are found to have uncapped ports decorated with hydroxyl groups mostly. Surface oxygencontaining groups specify the negative zeta-potential in all pH range studied (pH=3-11). The values of zeta-potential display an inverse dependence on the dispersion concentration in acidic and basic solutions. After modification of oxidized MWCNTs with HEMA their isoelectric point is shifted from pH=2 to pH=10. Repeated surface treatment with HEMA (MWCNTs-HEMA-HEMA), along with change of the nature of terminal groups, provides stable surface charge increasing with nanotubes concentration in the pH range of 3-9. The isoelectric point of MWCNTs modified with CTS occurs at pH=4.5. At relatively small zeta-potential values, which become more negative with a decrease in the nanotubes concentration, such suspensions are the most stable. Досліджено фізико-хімічні властивості, морфологію та характер поверхні вихідних і модифікованих 2-гідроксіетилметакрилатом (HEMA) і хітозаном багатошарових вуглецевих нанотрубок (БШВНТ). Вимірювання дзета-потенціалу БШВНТ проводили при різних рН розчину електроліту і концентраціях суспензії. Показано, що при окисненні БШВНТ відбувається їхнє дроблення з утворенням портів, що обрамлені переважно гідроксильними групами. Кисеньвмісні групи визначають негативний дзета-потенціал окиснених нанотрубок в досліджуваному діапазоні рН (3-11), але залежність дзета-потенціалу від концентрації дисперсії у кислому і основному середовищах обернена. Після модифікування БШВНТ НЕМА ізоелектрична точка зміщується з рН=2 до рН=10. Подовження ланцюжка прикріпленого до нанотрубок модифікатора (БШВНТ-HЕМА-HЕМА) разом із зміною кінцевих функціональних груп забезпечує позитивний і стабільний заряд поверхні, що збільшується симбатно концентрації нанотрубок в діапазоні рН 3-9. Ізоелектрична точка БШВНТ-хітозан близька до рН=4,5. За відносно невеликих значень дзета-потенціалу, який стає більш негативним зі зменшенням концентрації нанотрубок, такі суспензії є найбільш стійкими. Исследованы физико-химические свойства, морфология и характер поверхности исходных и модифицированных 2-гидроксиэтилметакрилатом (НЕМА) и хитозаном многослойных углеродных нанотрубок (МУНТ). Измерение дзета-потенциала МУНТ проводили при разных рН раствора электролита и концентрациях суспензии. Показано, что при окислении МУНТ происходит их дробление, а образующиеся порты обрамлены преимущественно гидроксильными группами. Кислородсодержащие группы определяют отрицательный дзета-потенциал окисленных нанотрубок в исследуемом диапазоне рН (3-11), но зависимость дзета-потенциала от концентрации дисперсии в кислой и основной средах обратная. После модифицирования МУНТ НЕМА изоэлектрическая точка смещается от рН=2 к рН=10. Удлинение цепочки прикрепленного к нанотрубкам модификатора (МУНТ-НЕМА-НЕМА) вместе с изменением концевых функциональных групп обеспечивает положительный и стабильный заряд поверхности, который увеличивается симбатно концентрации нанотрубок в диапазоне рН 3-9. Изоэлектрическая точка МУНТ-хитозан близка к рН=4,5. При относительно небольшом значении дзета-потенциала, который становится более отрицательным с уменьшением концентрации нанотрубок, такие суспензии являются наиболее устойчивыми.